Size-dependent UVB-mediated and mechanical breakdown of polystyrene nanoparticles in the presence of iron oxide - Ekvall, Mikael T.; Svensson, Raluca; Sudhakar, Swathi; Mani, Ethayaraja; Lundqvist, Martin; Cedervall, Tommy (Environmental Science: Nano, 2026)
Nanoplastics are increasingly being recognized as a global pollutant. However, relatively few studies report directly measured concentrations of nano- and microplastics in environmental samples, although available data suggest levels of up to 0.5 mg L−1 in lake water, which is surprisingly high. Their degradation in the environment, particularly under UV irradiation, is still poorly understood. Here, we investigated the effect of UVB irradiation on polystyrene nanoparticles of different sizes (99 nm to 200 nm) and evaluated whether iron oxide nanoparticles accelerate their breakdown. Particle size and mass changes were monitored using differential centrifugal sedimentation (DCS), dynamic light scattering (DLS), and nanoparticle tracking analysis (NTA). Our results show that UV-mediated degradation was size-dependent, with larger nanoparticles breaking down more rapidly than the smaller ones under identical mass concentrations. The addition of iron oxide nanoparticles accelerated the UVB-mediated breakdown of the 99 nm particles, leading to a >100-fold reduction in particle concentration and loss of toxicity in Daphnia magna assays after 111 days. Mechanical breakdown experiments demonstrated that the larger particles were more susceptible to size reduction than the smaller particles. Together, these findings suggested that small nanoplastic particles may accumulate in natural environments due to their slower degradation, but iron oxide could serve as an effective and low-cost remediation strategy for accelerating their breakdown and mitigating toxicity.
Publisher Copyright: This journal is © The Royal Society of Chemistry, 2026.